"I have learned that nothing is given for free": an exploratory qualitative evaluation of a social norms edutainment intervention broadcast on local radio to prevent age-disparate transactional sex in Kigoma, Tanzania - Lottie Howard-Merrill; Marjorie Pichon; Alice Witt; Revocatus Sono; Veronicah Gimunta; Enrica Hofer; Fatina Kiluvia; Mengi Alfred; Emmanuel Yohanna; Ana Maria Buller (BMC, 2024)
Abstract Background Promising evidence supports the effectiveness of edutainment interventions in shifting norms to prevent violence against women and girls and other harmful practices, yet further research into mechanisms and pathways of impact is needed to inform intervention development, delivery and scale-up. This exploratory qualitative evaluation examined the feasibility and indications of change in attitudes, beliefs, norms and behaviours following the broadcast of a radio drama aired to prevent age-disparate transactional sex in Kigoma, Tanzania. Methods Over seven weeks, six episodes were broadcast on local radio weekly, between November and December 2021 in Kigoma, targeting adolescent girls (aged 13-15 years) and their caregivers. Reflection sessions were conducted twice a week with 70 girls across seven schools, supplemented by after-school Girls' Club listening sessions for a subgroup of 30 girls. We conducted seven before and after focus group discussions, five with girls (n = 50), one with men caregivers (n = 9) and one with women caregivers (n = 9) and analysed them using thematic and framework analysis approaches. Results Overall, we found that while girls exhibited significant engagement with the drama, caregiver participation, particularly among men, was low. Thus, no clear changes were detected in men. We did not find any differences in impact based on listening sessions' attendance vs. home listening. We detected positive changes among girls and women in four thematic areas after listening to the drama: (1) participant's increasingly challenged perceptions about what kinds of girls and men take part in age-disparate transactional sex, what can be exchanged, and men's motivations for engaging; (2) there was a shift from attributing blame for age-disparate transactional sex relationships from girls to men; (3) girl's reported increased agency and confidence to avoid age-disparate transactional sex relationships; and (4) we found a heightened sense of responsibility and recognition for the role of parents, peers and community members in preventing age-disparate transactional sex. Conclusions These findings highlight the need for further implementation research to explore ways to effectively engage men. They also underscore the potential of engaging, evidence-based edutainment interventions in fostering spontaneous critical reflection about complex behaviours such as age-disparate transactional sex, and diffusing key messages among target populations without the use of organised diffusion activities.